The 1988–1989 transformation in Poland. The authorities, the opposition, the Church - Stachowiak, Paweł (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa, UAM, 2020)
The events that took place in Poland in 1988–1989 established a transformation model of which various elements tended to be replicated in other countries of the Soviet Bloc. Nevertheless, certain elements of the Polish transformation model were specific and unique, having sprouted from a specific historical context. The author of the paper proposes that the triad formed by “the authorities, the opposition and the Church” be considered a uniquely Polish aspect of the political and social transformation that took place after August 1980. The goal of this paper is to present this transformation with respect to each of the above three actors. An analysis of their concepts and actions leads to the conclusion that Poland should be considered an exceptional model of transformation in Central and Eastern Europe. The Polish transformation model featured a key and unique element, the Catholic Church – an institution that played a considerable role in making the 1988–1989 transformation non-confrontational.

Wydarzenia, które miały miejsce w Polsce w latach 1988–1989, stworzyły model transformacji, którego różne elementy były zazwyczaj powielane w innych krajach bloku sowieckiego. Niektóre elementy polskiego modelu transformacji były jednak specyficzne i niepowtarzalne, wyrastały z określonego kontekstu historycznego. Autor artykułu proponuje, aby triada utworzona przez „władzę, opozycję i Kościół” została uznana za wyjątkowo polski aspekt transformacji polityczno-społecznej, która miała miejsce po sierpniu 1980 roku. Celem artykułu jest przedstawienie tej trans formacji w odniesieniu do każdego z powyższych trzech aktorów. Analiza ich koncepcji i działań prowadzi do wniosku, że Polska powinna być uznana za wyjątkowy model transformacji w Europie Środkowo-Wschodniej. W polskim modelu transformacji znalazł się kluczowy i niepowtarzalny element, jakim jest Kościół katolicki – instytucja, która odegrała znaczącą rolę w uczynieniu transformacji 1988–1989 niekonfrontacyjną.
Przemiany lat 1988–1989 w Polsce. Władza, opozycja, Kościół
Keywords: Systemic change 1989; Model of transformation 1989; Poland 1989; Catholic Church 1989; zmiana systemowa 1989; model transformacji 1989; Polska 1989; Kościół katolicki 1989